Study of Mechanical properties of Sand extracted from Overburden of WCL Mines – the Effective Sustainable Sand Solution - et. al., B.V.Bahoria, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ecological environment concerns are being raised against exploitation of natural resources. The lack of consensus are mostly related to preserve soil beds from erosion and the fact of having natural sand as a filter media for ground water. For a period of time, coal industry in India is facing shortage of river sand due to new mining laws and its increasing demand in infrastructure expansion. The present study concentrates on study of extraction of sand from the overburdens of opencast mines of Coal fields and its feasibility as a fine aggregate in concrete. The surcharge soil spread over in mines needs to be removed for separation of coal to an external dump till ample space is produced for back filling by obtaining of land nearby coal carrying area. Moreover surcharge waste needs to be managed at the time of closure of mine for land acquisition. In present project study of physical properties of extracted sand from overburden and natural sand from river bed is compared and effort is made to utilize the waste generated in tones into sustainable sand solution.